Challenges and Opportunities for Adopting Innovation in Iraqi SMEs - Sultan, Abdulsatar Abduljabbar; Khalefa, Farah Basher; Saleh, Houshyar Abdulrahman; Riyadh, Hosam Alden (International Journal of Psychosocial Rehabilitation, 2020)
The adoption of innovation plays an essential role in transforming small and medium-sized companies into a knowledge economy. Nevertheless, Iraqi SMEs face various challenges in adopting innovation. The main objective of this study is to explore opportunities, the main challenges facing the adoption of innovation in Small and Medium Enterprises (SMEs) in the Kurdistan Region of Iraq. Evidence was gathered from the relevant previous studies and some discussions with the owners of companies that covered three governorates in the Kurdistan Region of Iraq (Erbil, Dohuk, and Sulaymaniyah). Researchers used qualitative research methodologies such as focus groups, and semi-structured interviews. The main major challenges facing SMEs in adopting the innovation are the lack of government support for innovation policies, also the wars and civil conflicts that lead to the travel of many minds and human skills. Accordingly, the study came out with a set of general recommendations that encourage small and medium-sized enterprises in the Kurdistan Region of Iraq to cooperate, exchange information and network interconnection, and prepare training programs in coordination with the government and civil society organizations to support and promote innovation support.